The Compressive Crushing of Powder Bed [Translated]† - Yoshiteru Kanda (KONA Powder and Particle Journal, 2014)
Roller mills have come to be actively used for the fine grinding of solids. In this paper, the compressive crushing of powder beds was carried out to study a roller mill. The effect of the applied load, the mass of feed and the particle size on the probability of crushing and on the crushing resistance were studied. The sample used was quartz. The following results were obtained: 1) When the applied load was constant, the deformation of the powder bed increased with the increase in the mass of feed and particle size. 2) The probability of crushing increased with the increase in the applied load, but the rate of increase of the probability gradually decreased. 3) The mass of the feed with a low crushing resistance was observed, and it had a certain range. This range narrowed with the decrease in the particle size. 4) The crushing resistance increased with the decrease in the particle size.† This report was originally printed in J. Soc. Powder Technology, Japan, 25(5), 292-296 (1988) in Japanese, before being translated into English by KONA Editorial Committee with the permission of the editorial committee of the Soc. Powder Technology, Japan.